Alexis Pogorelskin’s 2024 Book Hollywood and the Nazis on the Eve of War: The Case of The Mortal Storm, and Walter J. Ong’s Thought - Farrell, Thomas J. (New Explorations, 2025)
In 1937, the British novelist Phyllis Bottome published the anti-Nazi novel The Mortal Storm. In 1940, Metro-Golden-Mayer brought out the anti-Nazi movie The Mortal Storm, starring Margaret Sullivan and James Stewart. In 2010, thew DVD version of the 1940 MGM movie The Mortal Storm came out. In 2024, Alexis Pogorelskin published the book Hollywood and the Nazis on the Eve of War: The Case of The Mortal Storm. In the wide-ranging 6,169-word “Probe: Alexis Pogorelskin’s 2024 Book Hollywood and the Nazis on the Eve of War: The Case of The Mortal Storm, and Walter J. Ong’s Thought,” I mention the American Jesuit scholar Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955) of Saint louis University, where, over the years, I took five courses from him by name 61 times.